Pemodelan Struktur Perlapisan Bawah Permukaan Untuk Penentuan Bidang Gelincir Pada Daerah Rawan Longsor. (Studi Kasus Ruas Jalan Nasional 005 Lakuan – Laulalang Dan Ruas 006 Laulalang-Lingadan) - Hamad, Harly; Yunus, Ruslan Moh (JOURNAL TEKNIK SIPIL DAN INFRASTRUKTUR, 2017)
Characteristics of roads in Central Sulawesi at some point are an area of frequent landslides. The road segment in question, including the section 005 and section 006 which is a national road linking the province of Central Sulawesi and Gorontalo province. The link conditions that have often suffered landslides have disrupted access to transport and causing high transportation costs. This study aims to determine the geometry of the sliding plane at KM 509 and KM 513 using the method of geoelectric resistivity Wenner configuration with a path length measurement of 300 m and 5 m electrode spacing. The results of the study at two locations and modeling shows the layering structure resistivity value of which is at 100 Ωm - 300 Ωm and modeling results of  2-D geoelectric cross-section shows the sliding plane ground motion varies between 5 to 15 m. Value of resistance and sectional sliding obtained indicate that the location is vulnerable to landslides, and requires a comprehensive treatment to prevent landslides.